Prophylaxis for infective endocarditis: antibiotic sensitivity of dental plaque. Issue 4 (April 1983) - MacFarlane, T W; McGowan, D A; Hunter, K; MacKenzie, D
Abstract : The antibiotic sensitivity pattern of bacteria isolated from bacteraemia after dental extraction was compared with that of bacteria isolated from dental plaque samples from the same patient. The results supported the current practice of using penicillin and erythromycin empirically for prophylaxis. The prediction of the most appropriate antibiotic for prophylaxis using dental plaque samples was most accurate when the minimum inhibitory concentration (MIC) of plaque isolates were used. It appears that a predictive test using dental plaque may be of some value in patients with recent or long-term antibiotic therapy.